Diseño de un plan de comercialización para la pyme Betto Junior dedicada a la fabricación de jeans con tela obtenida a base del procesamiento de botellas reciclables en la ciudad de Quito - Asimbaya Perugachi, Jennifer Alexandra (2015)
This research, entitled "Designing a marketing plan for Betto Junior, micro enterprise dedicated to the manufacture of jeans cloth calculated from the processing recyclable bottles in Quito" has developed into six chapters. Framework in which the research is based is established; the situational analysis of the company Betto Junior therefore to design a strategic proposal aimed at improving the commercial management of the company, it is necessary to know its internal and environmental situation, to identify and characterize the critical success factors, and establish guidelines to promote competitiveness and market positioning. The market study, which allowed collecting information to identify market opportunities to be targeted ecological jean ECOJEAN develops. The proposed marketing plan for the line of organic pants Junior Betto, which defines strategic guidelines for marketing ECOJEAN products, ensuring they arrive effectively and efficiently to the customer, the company has increased competitive ability, who controls effective business management, and establishes tactics to develop. The financial perspective the feasibility of implementing the marketing plan for ecological jean line ECOJEAN, concluding that the proposal is financially viable and low-risk. Finally relevant research results are set by the conclusions and recommendations.